Treatment planning : in restorative dentistry and implant prosthodontics - Rodrigues, Antonio H.C. ([S.l.] : Quintessence Publishing Co, Inc., 2020)
'This book breaks down treatment planning into discrete steps that can be followed by every clinician every time to achieve predictable outcomes in restorative dentistry and prosthodontics, focusing on function, esthetics, and phonetics. It aims to teach clinicians how to consider the global picture of a patient's condition before tackling the individual issues that require treatment'--
Treatment planning : in restorative dentistry and implant prosthodontics -- Contents -- Preface -- Acknowledgments -- Chapter 1: A Rationale for Developinga Philosophy of Total Care -- Part one: The Planning Process: Identifying Existing Problems -- Chapter 2: Gathering and Organizing Clinical Data: Initial Consultation -- Chapter 3: Gathering and Organizing Clinical Data: Clinical Examination -- Chapter 4: Extraoral Examination -- Chapter 5: Intraoral Examination: Soft Tissues -- Chapter 6: Intraoral Examination: Hard Tissues -- Chapter 7: Intraoral Examination: Edentulous Areas -- Chapter 8: Intraoral Examination: Specialty Considerations -- Chapter 9: Interpreting the Collected Data, Determining the Diagnosis and Prognosis, and Establishing Treatment Objectives -- Part two: The Planning Process: Providing Solutions to Identified Problems -- Chapter 10: RestorativeTreatment -- Chapter 11: Conventional Restorative Dentistry -- Chapter 12: Implant-Supported Restorations -- Chapter 13: Treatment Plan Development -- Part three: Presenting Treatment Plans and Obtaining Consent to Treatment -- Chapter 14: Preparing the Patient to Make an Informed Decision -- Index.
Includes bibliographical references and index.
Keywords: Diagnosis, Oral -- methods; Mouth Diseases -- diagnosis; Dental Restoration, Permanent; Dental Prosthesis